Sexual development dysgenesis in interspecific hybrids of Medaka fish - Martinez-Bengochea, A. L. [UNESP]; Kneitz, S.; Herpin, A.; Nóbrega, R. H. [UNESP]; Adolfi, M. C.; Schartl, M. (Springer Nature, 2022)
Fish are amongst vertebrates the group with the highest diversity of known sex-determining genes. Particularly, the genus Oryzias is a suitable taxon to understand how different sex determination genetic networks evolved in closely related species. Two closely related species, O. latipes and O. curvinotus, do not only share the same XX/XY sex chromosome system, but also the same male sex-determining gene, dmrt1bY. We performed whole mRNA transcriptomes and morphology analyses of the gonads of hybrids resulting from reciprocal crosses between O. latipes and O. curvinotus. XY male hybrids, presenting meiotic arrest and no production of sperm were sterile, and about 30% of the XY hybrids underwent male-to-female sex reversal. Both XX and XY hybrid females exhibited reduced fertility and developed ovotestis while aging. Transcriptome data showed that male-related genes are upregulated in the XX and XY female hybrids. The transcriptomes of both types of female and of the male gonads are characterized by upregulation of meiosis and germ cell differentiation genes. Differences in the parental species in the downstream pathways of sexual development could explain sex reversal, sterility, and the development of intersex gonads in the hybrids. We hypothesize that male-to-female sex reversal may be connected to a different development time between species at which dmrt1bY expression starts. Our results provide molecular clues for the proximate mechanisms of hybrid incompatibility and Haldane’s rule.